Matter power spectrum and the challenge of percent accuracy - Schneider, Aurel; Teyssier, Romain; Potter, Doug; Stadel, Joachim; Onions, Julian; Reed, Darren S.; Smith, Robert E.; Springel, Volker; Pearce, Frazer R.; Scoccimarro, Roman (IOP Publishing, 2016)
Future galaxy surveys require one percent precision in the theoretical knowledge of the power spectrum over a large range including very nonlinear scales. While this level of accuracy is easily obtained in the linear regime with perturbation theory, it represents a serious challenge for small scales where numerical simulations are required. In this paper we quantify the precision of present-day N-body methods, identifying main potential error sources from the set-up of initial conditions to the measurement of the final power spectrum. We directly compare three widely used N-body codes, Ramses, Pkdgrav3, and Gadget3 which represent three main discretisation techniques: the particle-mesh method, the tree method, and a hybrid combination of the two. For standard run parameters, the codes agree to within one percent at k ≤ 1 hMpc‾1 and to within three percent at k ≤ 10 hMpc‾1. We also consider the bispectrum and show that the reduced bispectra agree at the subpercent level for k ≤ 2 hMpc‾1. In a second step, we quantify potential errors due to initial conditions, box size, and resolution using an extended suite of simulations performed with our fastest code Pkdgrav3. We demonstrate that the simulation box size should not be smaller than L = 0:5 h‾1Gpc to avoid systematic finite-volume effects (while much larger boxes are required to beat down the statistical sample variance). Furthermore, a maximum particle mass of Mp = 10⁹ h‾1Mʘ is required to conservatively obtain one percent precision of the matter power spectrum. As a consequence, numerical simulations covering large survey volumes of upcoming missions such as DES, LSST, and Euclid will need more than a trillion particles to reproduce clustering properties at the targeted accuracy.